Understanding the urban context and its challenges. - Frantzeskaki, Niki; Bach, Matthew; Mguni, Patience (Springer, 2018)
This chapter introduces a particular understanding of the urban context against the background of on-going societal change and persistent problems that threaten to induce disastrous change. The urban context is presented in relation to urban challenges, scopes of urban sustainability and the governance of the urban. Understanding urban context and its dynamics is important for finding the right approaches to tap into the potentials of cities and reroute their development pathways towards sustainability and resilience. The governance of urban sustainability transitions requires new forms of strategic environmental planning processes that integrate diverse sources of knowledge and diverse perspectives. The new planning processes need also to set connections between urban challenges and global, national and regional developments. The challenge remains for urban practitioners and scientists alike to take up a process-content thinking and to reflect on how to navigate societal complexity while mobilizing transformative societal potential towards action for sustainability.
Keywords: Stadtentwicklung; Nachhaltige Stadtentwicklung; Verstädterung; Umsetzung; Kooperation; Akteur; Transformation; Stadtsystem; Nachhaltigkeit; Stadtraum; Urban Governance